Knowledge management and additive manufacturing technology: A literature review - Godina, R.; Ferreira, I. A.; Brás, I.; Espadinha-Cruz, P.; Matos, F. (Proceedings of the 20th European Conference on Knowledge Management (ECKM 2019), 2019)
In the current business environment with increasingly dynamic and with numerous technological innovations, human resources and the generated know-how are volatile. Knowledge and the way it is shared and retained in organizations has become a source of competitive advantage. It is, therefore, necessary to develop tools to help companies manage their knowledge and use it to leverage value creation. In the case of companies that use or can use additive manufacturing technology, often associated with 3D printing, knowledge management processes are even more important since they are part of a disruptive and emerging industry with innovative and complex products whose business models' dynamics is not yet fully understood. Despite the great opportunities that this technology could provide, the uncertainties concerning its future developments and impacts on business models still remain. The goal of this literature review study is to get insights into publications that relate Additive Manufacturing Technology and Knowledge Management. The method used in this study is based on the analysis of all the data obtained from ISI Web of Science and Scopus. In terms of originality, this study aims to contribute and stimulate data-driven discussions regarding the possible impacts of the adoption of additive manufacturing regarding knowledge management strategies.